Kohbar Painting of Mithila, Nepal: A Study of Intangible Cultural Heritage - Dulal, Lok Nath; Adhikari, Radha; Singh , Sapna (Molung Educational Frontier, 2025)
Kohbar is a kind of painting that was created specifically on the wall and the floor of homes, and other monuments in the Mithila region. For this reason, it is regarded as an incredible piece of Maithili cultural art history. Thus, this paper has been produced to address the gaps and issues with the major goal to examine and highlight the idea of Kohbar painting, as well as its history, practices, creation techniques, types of materials, typologies, symbols, significance and an intangible cultural heritage unique to Mithila region and Nepal. The cultural importance and symbolic connotations that are woven into the elaborate patterns and motifs of Kohbar art have been explored in this study. Likewise, this study investigates the historical development, socio-cultural background, and ceremonial elements connected to Kohbar art using an interdisciplinary approach that combines art history, anthropology, and intangible cultural studies. Furthermore, this study looks at the relevance and difficulties that Kohbar art still faces today in the context of modernity and globalization, highlighting the importance of cultural revitalization and preservation initiatives. This article bases on qualitative information acquired in the form of both the primary and secondary data. The primary data have been collected from the Janakpur arts and culturally related stakeholders by using interview and group discussion whereas the secondary information has generated through the literature review.